Kontribusi Pura Dasar Buana Amerta Jati Siwa Buda dalam Pengembangan Bahan Ajar Prodi Teologi Hindu STAHN Mpu Kuturan Singaraja: Kontribusi Pura Dasar Buana Amerta Jati Siwa Buda dalam Pengembangan Bahan Ajar Prodi Teologi Hindu STAHN Mpu Kuturan Singaraja - Dewi, Ni Made Evi Kurnia; Kariarta, I Wayan; Heri, Komang Heriyanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Dasar Buana Amerta Jati Siwa Buda temple is a temple located in Tajun Village, Kubutambahan District, Buleleng Regency. The location of this temple is between a cliff and a forest. However, the uniqueness of the temple is reflected in the presence of different cultures in one temple area. In the innards of the temple there is a Meru building as a symbol of Hinduism and a stupa as a symbol of Buddhism. Until now there are still Buddhists who are active in praying to Dasar Buana Amerta Jati Siwa Buda temple, especially when the piodalan day arrives. Thus Dasar Buana Amerta Jati Siwa Buda temple provides space for Hindus and Buddhists to develop an attitude of tolerance. Moving on from this, the Dasar Buana Amerta Jati Siwa Buda temple has contributed to the development of teaching materials at the Hindu Theology Study Program STAHN Mpu Kuturan Singaraja. Contributions can be seen in the development of teaching materials for Shiva Siddhanta, Social Theology, and Hindu Cultural History courses. With the Dasar Buana Amerta Jati Siwa Buda temple as a learning medium, students do not only learn in theory. Both lecturers and students find it easier to develop learning activities.